Complete Epicardial Resynchronization Device Implantation in a Patient Who Underwent a Replacement of Mitral and Tricuspid Valve. Issue 2 (8th June 2011) - RICCIARDI, DANILO; ASMUNDIS, CARLO DE; CZAPLA, JENS; LA MEIR, MARK; BRUGADA, PEDRO; WELLENS, FRANCIS
<x xml:space="preserve">Abstract</x> A 71‐year‐old woman with severe nonischemic dilated cardiomyopathy and low ejection fraction with severe mitral regurgitation and tricuspid regurgitation and pulmonary hypertension underwent multiple valve repairs and cardiac resynchronization therapy implantation with epicardial shock leads. (PACE 2013; 36:e56–e58)